Post-harvest seaweed quality support in Pagarbatu Village, Sumenep, using SWSolar Dryer technology to create competitive seaweed farmers - Zuhri, Ach; Ahsan, Agung Firdausi; Saadah, Siti; Ghibran, Moh Iqbal; Aini, Anis Nur (IMPOWERMENT SOCIETY, 2026)
Seaweed is a leading commodity in Sumenep Regency. However, post-harvest quality remains low due to traditional drying methods, which, in turn, affects selling prices and farmer welfare. This community service program aims to improve the quality and competitiveness of seaweed farmers in Pagarbatu Village by applying SW-Solar Dryer technology. Implementation methods include outreach, management and production training, SW-Solar Dryer application, mentoring, and ongoing evaluation with "Kelana" fishing group partners. The results showed that the SW-Solar Dryer can reduce drying time from 2–3 days to just 5–8 hours. It maintains product hygiene because the process is carried out in a closed room. Moisture content produced also meets industry standards. Furthermore, the mentoring program encouraged diversification of processed seaweed-based products. This increased farmers' income and reduced dependence on collectors. Thus, the application of SW-Solar Dryer technology has proven effective in improving post-harvest management, expanding business opportunities, and creating more competitive seaweed farmers.